Effects of non-uniform heat generation/absorption and radiation on hydromagnetic dissipative flow over a porous nonlinear stretching surface with heat and mass fluxes - Agneeshwari, M.; Devi, S. P. Anjali (Zielona Góra: Uniwersytet Zielonogórski)
Forced convective heat and mass transfer flow of hydromagnetic, radiating and dissipative fluid over a porous nonlinear stretching sheet in the presence of non-uniform heat generation/absorption is investigated numerically.
Keywords: MHD; heat flux; mass flux; non-uniform heat generation/absorption